Is Participation in Primary Care Actions Leading to Better Behaviors in People With Diabetes? Results From the Amazon Region - Lucas Santos Fernandes; Johrdy Amilton da Costa Braga; Maria Natália Cardoso; Camila Fabiana Rossi Squarcini; Hércules Lázaro Morais Campos; Elisa Brosina de Leon (Journal of Primary Care & Community Health, 2025)
Background: Effective management of type 2 diabetes (T2DM) is critical, especially in regions with high social inequalities, such as Amazonas, Brazil. This study aimed to evaluate the impact of T2DM management activities offered by primary care settings on health behaviors. Methods: This is a cross-sectional study conducted in 10 cities of the Amazonas state in Brazil (n = 965). The study included individuals with T2DM who participate in activities on disease management offered by primary care settings. The health behaviors assessed included medication adherence, physical activity, and food and vegetable consumption. Results: There was a positive association between activity participation and medication adherence (OR = 0.51; 95% CI = 0.36-0.71). However, there was no association between participation and physical activity level, both for moderate (OR = 0.84; 95% CI = 0.58-1.22) or high levels (OR = 1.60; 95%; CI = 0.99-2.59) or daily fruit and vegetable consumption (OR = 0.61; 95% CI = 0.30-1.22). Conclusion: In conclusion, participation in activities offered in primary care positively impacts medication adherence. However, although participants received guidance on adhering to physical activity and healthy eating practices, no impact was observed in behavior changes in people diagnosed with T2DM.